FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENDAPATAN PETANI KOPI (Coffea sp) (Studi Kasus di Kecamatan Jambu Kabupaten Semarang) - Istianah Istianah; Dewi Hastuti; Rossi Prabowo (MEDIAGRO, 2015)
Coffee is one of the Plantation commodity that intensively cultivated by coffee farmers in Jambu District Semarang Regency This study aims to know the characteristics of coffee farmers and the factors that is affecting the level of coffee farmers’ income in Jambu District Semarang Regency. The technique of sampling area and respondents are conducted by purposive sampling method. The sample of populations are taken by 69 respondents of the coffee farmers, 13 respondents of Kelurahan Village, 26 respondents of Bedono Village, and 30 respondents of Kebondalem Village in Jambu District Semarang Regency. From the study found that the characteristics of the coffee farmers in Jambu District Semarang Regency are the average of the land area is 2,802 m2. The farmers education average is graduated from primary school (elementary school) is 73.91%, it indicates that the farmers education is low and under 9 years from the basic education. The average farmers age is 48 years old is 44.93%. The cost analysis is obtained by the total cost Rp. 769 820, -. The analysis of revenue is obtained by the result of Rp 12.205.000, while the analysis of the income is earned by Rp 11.435.180. The factors that is affecting of the coffee farmers income in Jambu District Semarang Regency is the number of trees, experience, and education. The number of trees with t value counted 8.000 and the significant is 0.000 means that it has significant effect on the income in the real level of 1%. The experience with the t value is 1.684 and the significant is 0.097 means that it has significant effect on the income in the real level of 10%. The education with t value counted 2.010 and significant of 0.049 means that it has significant effect on the income in the level of 5%. Based on data analysis by using multiple linear regression is known that the determination coefficient (R2) is 0.864 means that 86.4 percent of the variation ups and downs of the coffee farmers' income is affected by the factors that is in this study and the remaining of 13.6 percent is influenced by the other factors that is not incorporated into the study variables.   Keywords: Coffee  farmers’ income, Multiple Linier Regression, Jambu District Semarang Regency.